Challenges of graduates with hearing disabilities in the hospitality industry - Ungku Zainal Abidin, Ungku Fatimah; Mat Yusoff @ Mohd Yusof, Norhayati; Wan Abdullah, Wan Arnidawati; Mohamad, Siti Fatimah; Alias, Roslinda (Zes Rokman Resources, 2024)
The Malaysian government has provided educational opportunities to youths with hearing disabilities to raise their socio-economic status. This group has been provided with the necessary skills in selected institutions to fulfil significant roles in the country's economy, specifically in the hotel and food and beverage (F&B) industries. This effort corresponds with the United Nations' 2030 Agenda and Sustainable Development Goals (SDG), which have greatly enhanced the rights of people with disabilities as they aim to raise the standard of living worldwide without leaving anyone behind. Despite higher education having the potential to break down barriers and make progress in promoting inclusivity in the institutions, youth with hearing disabilities who have completed their education still face obstacles in their pursuit of employment and career development in the hospitality workforce. Thus, this study explores the challenges of graduates with hearing disabilities who intend or are already working in the hospitality industry. Semi-structured interviews were conducted with nine (9) informants who graduated with Certificates in Basic Culinary, Basic Pastry, or Hotel and Catering from four public institutions in Malaysia with the help of a professional sign-language interpreter. The data that was gathered was subjected to thematic analysis. The findings revealed communication barriers, discrimination, workloads, and co-workers are the challenges faced by graduates with hearing disabilities in the field of employment in the hospitality industry. The situation has left graduates feeling disappointed and undervalued in the industry. This study will aid hospitality educational institutions by allowing them to examine and modify their curriculum to meet industry standards. Besides, government funds provided to hospitality schools via the Ministry of Education help youth with hearing disabilities acquire knowledge and skills that will be valuable when they join the industry and contribute to the economy.